Study on the Effective Material Basis and Mechanism of Traditional Chinese Medicine Prescription (QJC) Against Stress Diarrhea in Mice - Zhang, Yuefeng; Yu, Fei; Hao, Jingyou; Nsabimana, Eliphaz; Wei, Yanru; Chang, Xiaohan; Liu, Chang; Wang, Xiaozhen; Li, Yanhua (Frontiers in Veterinary Science, 2021)
Stress diarrhea is a major challenge for weaned piglets, which restricts the production efficiency of pig production and leads to huge economic losses. The traditional Chinese medicine prescription (QJC) composed of Astragalus Membranaceus (HQ), Zingiber Officinale Roscoe (SJ) and Plantago Asiatica L. (CQC) with obvious anti-stress diarrhea effect has been developed by our laboratory. However, the active compounds, potential targets and mechanism of anti-stress diarrhea is still not clear and needs further investigation. Our study was to verify the bioactive compounds of QJC and relevant mechanism of anti-stress diarrhea through network pharmacology and in vivo experimental studies. We employed network pharmacology to predict the biological active ingredients and anti-stress diarrheal mechanism of QJC. After establishing a successful stress-induced diarrhea model, histomorphology of Intestinal mucosa, RT-qPCR and relative indexes to verify the therapeutic effect of QJC on diarrhea. First, based on the network pharmacology, we identified 35 active components and 130 KEGG pathways in QJC. From this we speculate that quercetin, luteolin, kaempferol, scutellarin and stigmasterol as the main bioactive compounds and assumed that antidiarrheic effect of QJC was related to PI3K-Akt signaling pathway. Next, the group of QJC and stigmasterol both performed a great effect in anti-diarrheal in vivo experiments. And the RT-qPCR indicated that QJC and its bioactive components increased the expression levels of PI3K and Akt, inhibited the dephosphorylation of PTEN, activated the PI3K-AKT signaling pathway to relieve stress-induced diarrhea. At the same time, we found that QJC can alleviate the pathological condition of small intestine tissue and improve the integrity of intestinal barrier. In brief, our study showed that traditional Chinese medicine QJC, quercetin, luteolin, kaempferol, scutellarin and stigmasterol can alleviate the pathological condition of small intestine tissue and relieved stress-induced diarrhea by increasing the expression levels of PI3K and Akt and inhibiting the expression levels of PTEN.